Rebranding of Tourist Destinations: A Case Study of Mount Kemukus - Pandan Wibowo; Kurniawati Darmaningrum; Darsono (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research aims to analyze the impact of (1) rebranding, (2) facilities, and (3) promotion on tourist visits to Mount Kemukus. Methodology: The data sources in this research are primary and secondary data. Data collection techniques in this research are Interviews, Observations, and Documentation. Data analysis is conducted using Data Reduction, Data Display, and Conclusion Drawing. Main Findings: This research indicates that: 1.The initial negative stigma originated from a miscommunication between the key keeper of Pangeran Samudra's Tomb and tourists from outside Java. 2.The management of The New Kemukus requires expansion and addition of parking spaces for tourist comfort. In terms of communication, there are already directional signs and information services to prevent tourists from feeling confused. The available services are sufficient for tourist comfort, and the environment is supportive of family tourism. Novelty/Originality of this study: This research also concludes that rebranding efforts can be effective in changing the image of a tourist destination, but ongoing efforts are needed to maintain momentum and attract a steady flow of tourists.